Application of the Project Method in Computer Science Classes - Ilyasova Zukhra Kenesbayevna; Zinakhan Abdirazakovna Urimbetova (International Journal on Orange Technologies, 2022)
The project method, which focuses on autonomous and group activities to solve applicable problems and increase students' competency, is reintroduced in this article.